REVIEW OF 3-STORY PLATE STRUCTURAL DESIGN OF SOLOK POLRES FLAT BUILDING, WEST SUMATRA - Hardi Wijaya; Adrian Fadhli; Al Azhar (Journal of Scientech Research and Development, 2024)
The 3-storey building of the Solok District Police Flat located in Koto Gaek Guguak, Gunung Talang District, Solok Regency is a state building that functions as a means of carrying out state duties by the Police at the Solok District Police to maximize performance. Therefore, a building that suits the needs and has a stable and strong structure that can withstand static loads and potential disasters such as earthquakes is needed, because the Solok Regency area is a fault area prone to earthquakes. The initial design of the building's upper structure seemed uneconomical, especially in the floor plate section. The author reviewed the planning of the upper structure of the floor plate section by referring to building construction regulations and earthquake resistance. This research uses a descriptive qualitative method. Data were collected through literature review and field observation. The data was analyzed using the Microfoft Excell application. Analysis of the comparison of the initial design with the construction design plan shows that the results of the calculations carried out have a reinforcement shrinkage on the S1 type floor plate of 37.50% and a reinforcement shrinkage on the S2 type floor plate of 25.00%.